MENGHIDUPKAN KEMBALI IDENTITAS KELURAHAN KEBON JERUK MELALUI STRATEGI PLACEMAKING - Wong, Cellina; Lianto, Fermanto (Jurusan Arsitektur dan Perencanaan, 2024)
Identity is an important factor in the meaning of a place. Identity here is formed from the authentic elements of a place that differentiate it from others. However, over time, a place can become placeless due to physical, economic or social degradation, which is known as a placeless place. Kebon Jeruk is one of them that experiences the placeless place phenomenon. It is named Kebon Jeruk because of its identity as the largest citrus fruit producing area since Dutch colonialism. It started with the implementation of a forced planting system policy which in this area focused on growing oranges. Shortly after independence, this area still maintained its identity as an orange plantation. The farmers grew crops in their yards without any coercion from the Dutch and then sold the harvests to the market, and some for their own consumption. This is a symbolic bond between nature and humans living side by side and complementing each other. However, this area has failed to adapt to an era where the identity of the name Kebon Jeruk is now not reflected in an area that is densely populated with residential areas and offices. Therefore, an architectural approach is needed with the aim of restoring the area's identity both in terms of culture and history, which can build a sense of place attachment among residents so that it has a long-term impact. With the programming method, it combines two main programs in the form of urban farming and edutainment into a new program, namely the agrotourism program. It is hoped that it can provide awareness of the importance of preserving the identity of Kebon Jeruk, as oranges have become a flavoring medium to build a sense of place attachment and have one's memory. Keywords: Edutainment; Kebon Jeruk; Urban Farming; Placeless Place; Placemaking Abstrak Identitas menjadi faktor penting akan pemaknaan place dari suatu tempat. Identitas disini terbentuk dari unsur otentik suatu tempat yang membedakannya dengan yang lain. Namun seiring berjalannya waktu, place dapat berubah menjadi placeless dikarenakan degradasi dari segi fisik, ekonomi, atau sosial yang dikenal sebagai placeless place. Kebon Jeruk merupakan salah satunya yang mengalami fenomena placeless place. Dinamakan Kebon Jeruk karena identitasnya sebagai kawasan penghasil buah jeruk terbesar sejak penjajahan Belanda. Berawal dari diberlakukan kebijakan sistem tanam paksa yang pada kawasan ini berfokus menanam jeruk. Sesaat setelah kemerdekaan, kawasan ini tetap mempertahankan identitasnya sebagai perkebunan jeruk. Para petani bercocok tanam di halaman rumahnya tanpa adanya paksaan dari Belanda yang kemudian hasilnya dijual ke pasar, dan sebagian untuk konsumsi sendiri. Hal ini menjadi ikatan simbolis antara alam dan manusia hidup berdampingan saling melengkapi. Akan tetapi, kawasan ini gagal beradaptasi dengan zaman dimana identitas dari nama Kebon Jeruk sekarang tidak tercermin pada kawasan yang padat pemukiman, dan perkantoran. Oleh karena itu, dibutuhkan pendekatan arsitektural dengan tujuan mengembalikan identitas kawasan baik dari segi budaya, dan sejarah terkandung yang dapat membangun rasa place attachment para warga sehingga berdampak secara jangka panjang. Dengan metode disprogramming menggabungkan dua program utama berupa urban farming dan edutainment menjadi suatu program baru, yakni program agrowisata. Diharapkan dapat memberikan kesadaran akan pentingnya melestarikan identitas Kebon Jeruk sebagai jeruk menjadi media perasa untuk membangun rasa place attacment dari memori seseorang.